Decapentaplegic signaling regulates Wingless ligand production and target activation during Drosophila wing development. Issue 7 (25th December 2019) - Li, Yunlong; Zhang, Fengchao; Jiang, Na; Liu, Tong; Shen, Jie; Zhang, Junzheng
Abstract : The Decapentaplegic (Dpp) and Wingless (Wg) signaling pathways are essential for animal development. However, how these two signals are integrated in distinct tissues is not fully understood. Here, we describe a novel mode of Dpp‐Wg crosstalk during Drosophila wing development. We show that the canonical Dpp signaling is required for Wg target gene activation. In addition, Dpp signaling inhibits the transcription of wg through the schnurri (shn) repressor complex. A Dpp‐responsive shn/pMad/Med silencer element (SSE) is identified in the genomic loci of the wg gene. ChIP analysis suggests that shn interacts with this element in vivo . Our findings support a model in which Dpp signaling plays a dual role in transcriptional regulation of both the wg gene and downstream targets. Abstract :